Pengaruh Supervisi Akademik Kepala Sekolah Dan Teamwork Terhadap Tingkat Kepuasan Kerja Guru Di Smp Sekecamatan Sindang Kelingi - Irawan, Andi; Somantri, Manap (Manajer Pendididikan, 2023)
The study was conducted to analyze the effect of academic supervision and teamwork on the level of job satisfaction of junior high school teachers in Sindang Kelingi District, Rejang Lebong Regency. The research sample was 50 teachers using a total sample. Data collection using a questionnaire. The data analysis technique used statistical correlation test using Pearson product moment analysis and regression test. The results showed that: (1) There was a positive relationship between academic supervision and teacher job satisfaction, (2) There is a positive relationship between teamwork and teacher job satisfaction,(3) There is a joint relationship between academic supervision and teamwork with job satisfaction by 52% of yunior high school teachers in Sindang Kelingi District, Rejang Lebong Regency.